2017
DOI: 10.1039/c6ob02666d
|View full text |Cite
|
Sign up to set email alerts
|

Tetraceno[2,1,12,11-opqra]tetracene-extended tetrathiafulvalene – redox-controlled generation of a large PAH core

Abstract: Two tetraceno[2,1,12,11-opqra]tetracene-extended tetrathia-fulvalenes were prepared and found to undergo reversible conversion into their planar polycyclic aromatic hydrocarbons (PAHs) upon electrochemical oxidation - at potentials probing the best valence bond representations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 30 publications
1
17
0
Order By: Relevance
“…[6b-d] Remarkably, BT 1 is more stable than TIPS-PEN at the beginning of the photo-oxidation process even though its ionization potentiala nd electron affinity are lower.T his result confirms that the stability of the BT scaffold relies on its high degree of aromaticity. [15] The structures of BT 1, BT 2 and BT 3 were confirmed by Xray crystallography (Figure 4). Theoretical calculations of electronic couplings between molecules in interaction were performed using DFT at the PW91/TZP level to evaluatet he potential of these materialst ob eu sed in OFET devices.…”
Section: Resultsmentioning
confidence: 83%
“…[6b-d] Remarkably, BT 1 is more stable than TIPS-PEN at the beginning of the photo-oxidation process even though its ionization potentiala nd electron affinity are lower.T his result confirms that the stability of the BT scaffold relies on its high degree of aromaticity. [15] The structures of BT 1, BT 2 and BT 3 were confirmed by Xray crystallography (Figure 4). Theoretical calculations of electronic couplings between molecules in interaction were performed using DFT at the PW91/TZP level to evaluatet he potential of these materialst ob eu sed in OFET devices.…”
Section: Resultsmentioning
confidence: 83%
“…For example, acenes with a buttery structure were originally studied a couple of decades ago, and the buttery structure can be changed to a at structure by electrochemical oxidation. [18][19][20][21] Through precise molecular engineering of the core structure of oligoacenes, Tang and co-workers have shown that quinoidal derivatives of oligoacenes can exhibit aggregation induced restricted intramolecular vibration (RIV). 22,23 AIE is counterintuitive since aggregation tends to quench photoluminescence of organic chromophores.…”
Section: Introductionmentioning
confidence: 99%
“…Keywords that highlight acene-type PAHs with zig-zag periphery range from singlet fission 17 21 , auspicious charge carrier mobilities 22 , 23 , to amplified spontaneous emission 24 , and enlarge the interest in PAHs by the fields of spintronics and molecular magnetism 25 - 27 . Recently, various research groups reported on substituted angularly fused-tetracenes 28 32 , which overcome the low stability of linear acenes, by increasing the intrinsic number of Clar’s-sextets 33 . These fused structures showed excellent performances in field-effect transistors 28 , 29 , 31 , 32 .…”
Section: Introductionmentioning
confidence: 99%